2015
DOI: 10.33549/physiolres.933205
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1 Modulation in Rat Model of Acetaminophen-Induced Hepatotoxicity

Abstract: Sirtuin 1 (SIRT1) is involved in important biological processes such as energy metabolism and regulatory functions of the cell cycle, apoptosis, and inflammation. Our previous studies have shown hepatoprotective effect of polyphenolic compound resveratrol, which is also an activator of SIRT1. Therefore, the aim of our present study was to clarify the role of SIRT1 in process of hepatoprotection in animal model of drug-induced liver damage. Male Wistar rats were used for both in vivo and in vitro studies. Hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In addition, we have provided new mechanistic insights to the recent work of Wojnarova et al (57) who reported decreased SIRT1 activity in rats treated with APAP that was reversed by resveratrol or the SIRT1 activator CAY10591. Wang et al (52) reported that resveratrol treatment was associated with elevated SIRT1 protein in mouse livers that were protected from APAP hepatotoxicity.…”
Section: Figmentioning
confidence: 65%
“…In addition, we have provided new mechanistic insights to the recent work of Wojnarova et al (57) who reported decreased SIRT1 activity in rats treated with APAP that was reversed by resveratrol or the SIRT1 activator CAY10591. Wang et al (52) reported that resveratrol treatment was associated with elevated SIRT1 protein in mouse livers that were protected from APAP hepatotoxicity.…”
Section: Figmentioning
confidence: 65%
“…In addition, treatment with a SIRT1 activator has been shown to have no effect on early injury (6 hours) after APAP but decreases late injury (24 hours), while enhancing mitochondrial biogenesis and liver regeneration. Furthermore, resveratrol, which activates SIRT1, protected against APAP liver injury (76,77). Taken together, conflicting evidence exists regarding the role of SIRT1 in acute injury models.…”
Section: Discussionmentioning
confidence: 99%
“…The mean diameter of Glomeruli's space was measured in all groups of rats on day 8 and the relationship between Glomeruli's space and TNF-α, IL-6, MDA, and SOD are shown in (A -D), respectively. in rats have been reported (Wojnarová et al, 2015;Elbe et al, 2018). A recently published work (Elbe et al) reported a significant inhibition of liver iNOS immunostaining and hepatocyte ultrastructure damage by RES (10 mg/kg) given 20 minutes post APAP (1 g/kg) injection in rats.…”
Section: Discussionmentioning
confidence: 99%